International Conference on ‘Disability Studies: Heading in the right(s) direction?: November 20th – 22 2014th, Center of Excellence for Disability Study and Faculty of Social Sciences (Brochures) - Ali, Kamsiah; Ling How, Kee (Universiti Malaysia Sarawak (UNIMAS), 2010)
BACKGROUND